Relationships between quality of life, sleep problems, and sleep quality in patients with chronic idiopathic urticaria. (5th April 2022) - Ates, Hale; Firat, Selma; Buhari, Gozde Koycu; Keren, Metin; Cifci, Bulent; Erkekol, Ferda Öner
Abstract: Background: In this study, we aimed to evaluate the sleep quality among chronic urticaria patients using the Chronic Urticaria Quality‐of‐Life Questionnaire (CU–Q2oL), sleep quality assessment tools, and polysomnography and to investigate any relationships between the obtained results. Methods: The study included 21 patients diagnosed with chronic spontaneous urticaria and 19 healthy controls. We recorded the patients' sleep quality data, including CU–Q2 oL, Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), and polysomnography results. Result: Patients in the chronic urticaria group were more likely to have an ESS score of ≥10 (52.4% vs. 5.3%, p  = 0.004) and an apnea‐hypopnea index of ≥5 (44.4% vs. 5.3%, p  = 0.017) compared to the control group. In the patient group, the CU–Q2 oL total score was positively correlated with sleep latency ( r  = 0.713, p  = 0.004) and PSQI–C1 score ( r  = 0.726, p  = 0.005), while it was negatively correlated with urticaria duration ( r  = −0.579, p  = 0.015), apnea‐hypopnea index ( r  = −0.607, p  = 0.021), longest apnea duration ( r  = −0.583, p  = 0.029), total number of respiratory events ( r  = −0.618, p  = 0.018), and apnea count ( r  = −0.686, p  = 0.007). Conclusion: We conclude that sleep‐related problems exist among a considerably large proportion of patients with chronic spontaneous urticaria.